TECHNOLOGY OF FRUIT SAUCES FOR HEALTH PURPOSES - ANTONENKO АRTEM; BAL-PRYLYPKO, LARISA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Among the wide range of culinary products, an important place is occupied by sauces, which have a high consumption quality. By combining products and sauces, you can expand the range of culinary products, regulate nutritional and biological value, caloric content, cost price, product price, and production profitability. In order to increase the biological and nutritional value, we investigated the possibility of developing the technology of fruit sauces based on vegetable hydrocolloids, calcium lactate, protein and fat additives. The most problematic issue in the technology of sauces is ensuring their colloid stability, which is determined, first of all, by the effectiveness of the structure-forming agents of low- or high-molecular substances and their complexes. Of particular interest are high-molecular structure-formers represented by proteins of plant origin and polysaccharides. Mathematical methods based on the physicochemical parameters of the chemical composition of sauces determined the rational ratio of protein and fat additives, dietary fibers Fibregum and Litesse, pectin and calcium lactate as 5:3:3:2:2. Analysis of the chemical composition of control and test samples of sauces shows an increase in protein content by 8.5 and 6 times, fats by 1.1 g, dietary fibers by 6.8 and 7.8 times compared to the control. The mineral composition improved by increasing the content of potassium by 95% and 155%, calcium by 33 and 21 times, magnesium by 3.8 times, phosphorus by 5.2 and 4.2 times, iron by 74% and 293%, respectively. The content of vitamins increased significantly: B1 – 6.7 and 7 times, B2 – by 76.5% and 167%, PP – 40% and 14 times, C – 40% and 17.5%, respectively. The developed quince and persimmon sauces have a better biological value, and in terms of organoleptic indicators, they are close to the control samples. Based on the physiological properties of the studied raw materials, the developed products can be recommended for inclusion in the diets of workers working in hazardous industries, people living in polluted areas and for all age groups of the population.